Role of mother’s perceptions on their child development on early detection of developmental deviation - Pudji Andayani; Soetjiningsih Soetjiningsih (Indonesian Pediatric Society, 2001)
This report aimed to assess mothers’ perceptions on normal and deviation of development in their children. The study was done in underfive children and their mothers from May 1st 1999 to June 30th 1999 who visited the Nutrition, Growth & Development Clinic of the Child Health Department, Sanglah Hospital, Denpasar. A total of 76 children between 2 and 59 months of age and their mothers were enrolled. Data were collected by interview with mothers concerning the following items: perception of their children development, age of child, sex, mother’s education, mother’s job, number of sibling, and mother ability in making referral decisions. Denver II screening test was administered to each child to identify of development status as a gold standard. Sixteen (21%) children was identified as having developmental deviation (by mother’s perception) and 21 (28%) by authors using Denver II screening test. The mother’s perception sensitivity was 67% and specificity was 97%. There were no significant differences of development status perception according to child’s age, mother’s education, mother’s job, and number of sibling. Most of mother’s perceptions about normal development were if the body weight increased and had no disability. Most of the sources of information about development was from the relatives. Thirteen of 21 children who had developmental deviation were referred by mothers. We conclude that mother’s perception can be used as early detection of developmental problems. Mother’s concerns of their children growth development had focused on again body weight, physical developmental and gross motor skill.